The Potential of Biogas Renewable Energy from Waste Management in the Education Tourism Talangagung Landfill Kepanjen - Raditya Wahyu Imansyah; Bagyo Yanuwiadi; Sri Utami (The Indonesian Green Technology Journal, 2019)
Waste is a remnant produced from human activities such as; household, commercial, office, industrial, etc. Waste is considered to have no value because it cannot be reused so that some people do not care about the impact of waste. The accumulation of waste that accumulates every day will harm the environment and society. The incoming waste to be processed at Talangagung Landfill comes from: Settlements, markets, Sub-Landfill, hospitals, offices, companies and highway services. In 2018 the Talangagung landfill receives 48,063.37 tons/year of waste. The largest source of waste entering the Talangagung landfill comes from settlements of 54%, the market by 22%, sub- landfill by 15%. Talangagung landfill educational tourism is one of the pilot landfills that use a controlled landfill system to manage waste to minimize negative impacts on the environment and society. The waste that enters the Talangagung landfill will be processed into biogas. Renewable energy produced from Talagagung landfill in the form of methane gas arising from waste decay. The potential for waste management into biogas can be calculated using the scholl canyon method from Talangagung landfill waste data in 2018. The results of the calculation of the gas produced are 183,558 m3 / year. The gas produced is assumed to only be captured at 75% with the composition of methane gas at 50% -55% of the total gas produced. The resulting methane gas has decreased to reach 31,897.6 tons/year in the 40th year. This is because waste that experiences an anaerobic phase experiences nutrient reductionKeywords: Controlled landfill, Renewable energy, Methane, Waste